Recent Update in The Management of Childhood Nephrotic Syndrome - Kayes, Mohammad Imrul (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Nephrotic Syndrome (NS) is a common renal disease seen in children. Children who go into complete remission following treatment with corticosteroids are classified as having steroid sensitive NS. In developed countries over 80% of children with idiopathic NS have steroid sensitive disease. The exact pathogenesis of this condition remains elusive. Podocyte injury and proteinuria are the two main issues in the pathogenesis. Recent studies suggest release of cytokines by T-cells as well as a strong contribution of Bcell immunity. Genetic studies have reported human leucocyte antigen (HLA) class II antigens DR and DQ associations linked to steroid sensitive NS. Most children with steroid sensitive NS have multiple relapses and a significant percentage also develop steroid dependent NS. Diuretic- resistant edema also a clinical problem to manage these patients. These children receive multiple courses of steroids and are at high risk of developing steroid toxicity. Patient with frequent relapses who develop steroid dependency thus require alternative treatment. Steroid resistant NS considers when failure to response within 8 weeks of steroid therapy. Steroids sparing agents used include levamisole, cyclophosphamide, mycophenolate mofetil (MMF), calcineurin inhibitors (cyclosporine and tacrolimus), rituximab and vincristine; these agents have greatly reduced the adverse effects seen with long-term use of steroids; so therapy needs to be individualized to achieve optimal care of each child. J Bangladesh Coll Phys Surg 2016; 34(1): 26-32